Faktor Analisa Dengan Pemberian Asi Eksklusif Terhadap Umur Dan Pekerjaan Ibu Menyusui - Susanti, Susanti; Rabuana, Susi; D, Yuliana; Sallo, Andi Kamal M (Barongko: Jurnal Ilmu Kesehatan, 2024)
Breast milk (ASI) is a fluid that comes out of the mammary glands of a mother's breasts which contains various nutritional substances that are crucial in supporting the development and growth of toddlers. Breast milk is divided into 3 types, namely colostrum, transitional breast milk, and mature breast milk. Exclusive breast milk is breastfeeding that is not accompanied by any other food or drink supplementation except medication. Exclusive breast milk is given for the first 6 months, after this period breast milk is unable to meet mineral needs so it must be accompanied by complementary food for breast milk (MP ASI). This study aims to determine the relationship between maternal age and employment and exclusive breastfeeding at the Mamuju Community Health Center. This research is an analytical survey with a cross-sectional approach. The results of the analysis of the age of mothers with exclusive breastfeeding obtained a p-value of 0.007 (p<0.05) while the analysis of the work of mothers with exclusive breastfeeding resulted in a p-value of 0.000 (p<0.05). In conclusion, there is a relationship between the mother's age and occupation and exclusive breastfeeding in the Mamuju Community Health Center working area.